Invasive birds global trends and impacts - Downs, Colleen T.; Hart, Lorinda A (CABI, 2020)
"Divided into three sections, this book provides detailed information on the 32 global avian invasive species listed by the Invasive Species Specialist Group (ISSG). It also offers an assessment of avian invasions from a biogeographic perspective, and considers the ecological impacts of these invasive species"--